"Microfinance and Rural Market Dynamics: An Empirical Case Study of SHG-Led Commercial Activities in Holenarasipura Taluk" (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Micro Finance is recognized as a financial service which provides small loans to the needy by exploring different savings from poor and low-income group people who does not have any kind of access to regular banking services. This type of financial service provides loans to those individuals who would like to start small and micro businesses. It intends to improve their income levels by enhancing their standard of living. The prime objective of this kind of finance is to support small entrepreneurs by providing financial assistance without bargaining for a mortgage. It tries to promote rural entrepreneurship and intends to develop socio-economic conditions of the lowest strata of the society.The current study intends to examine the influence of Micro-Finance on the development of commercial activities undertaken by the Self Help Group Members in Holenarasipura Taluk of Hassan District. It also tries to understand the market dynamics involved in this process. It is based on a questionnaire survey of selected SHG members involved in various commercial activities such as, tailoring, petty shops, dairy farming, small handicrafts, fisheries, agricultural oriented businesses located in Holenarasipura Taluk. A total of 100 questionnaires were served and evaluated using various statistical tools such as, percentage analysis, mean score analysis, and factor analysis, chi-square test, correlation and regression analysis. The findings of this study reveal that any kind of access to micro-finance has contributed significantly in financial inclusion of rural masses. It has resulted in enhancing rural entrepreneurship, increased rural house hold income and expanded market opportunities for rural farming. It is also found in the process of analysis that there exists a positive relationship between availability of credit and growth of business. Self Help Groups have facilitated in creating saving habits, rural employment generation, empowering rural women and there by contributing towards socio-economic growth of rural areas. This has contributed significantly in sustainable rural development. It is suggested that strengthening financial literacy programs, increasing credit support through SHGs and linking rural markets to the main stream markets will maximize the participation of rural entrepreneurs.